(untitled) (Fiep Bulletin - online, 2014)
Currently 275.000 cardiacsurgeries are accomplished in all over the world, with operative mortality around 1 to 15%. In spite of technological advances, the pulmonary complications (PCs) are often observed and the commitment of pulmonary function portrays an important cause of morbidity and mortality in the PO. The non-invasiveventilation (NIV) have been used in orderto reverse orsoftenthatfact. Was evaluate whether non-invasive continuous positive pressure (CPAP) applied in posoperative (PO) of cardiac surgery (CS) promotes increasing in pulmonary volumes. The sample was consisted by individuals under went to CS at Hospital Santa Cruz. The pre-operative evaluation and the spirometry were accomplished to measure the pulmonary volumes in pre-operative, PO and pre-discharging. About the 1º day after the extubation, CPAP was applied with variable PEEP between 8 and 15 cmH2O, around 15 and 20 minutes, twice a day, untildischarging. Eightpatientswereevaluated, withage of 47,5± 17,44 yearsoldand IMC around 27,73±4,85 Kg/m2. Three (03) individuals showed normal weight, two (02) showoverweight, and three (03) showed obesity type I. The following variables showed significant reduction when compared to the values of PO to pre-operativeones: CVF, VEF1, PEF and FEF25-75(p<0,002), (p< 0,010). Moreover, in CVF, PEF, FEV1/CVF and FEF25-75(p<0,005) (p<0,30), there was a significant improvement when compared the pre-discharging volumes to posoperativeones.The following variables indicate that NIV contributed for the increasing for pulmonary volumes of patients under went to cardiac surgery.